Modernization, Globalization, and Women in Argentina : Their Changing Roles in the Economy and in Society - Wieseman, Laurelyn (My University, 2012)
A historical analysis of the status of women in Argentina reveals a picture of a society that nearly defies description. In order to understand the socioeconomic status of Argentine women today, this study involves a historical analysis of women's status from the early 16th century until today, with particular emphasis on the globalization and economic restructuring policies that took place during the 1990s and 2000s.
Color poster with text, photographs, graphs, charts, and tables.
Keywords: Women--Argentina--Social conditions; Women--Argentina--History; Argentina--Relations--Foreign countries; Women--Argentina--Economic conditions; Sex role--Argentina; Posters